2011
DOI: 10.3396/ijic.v7i3.021.11
|View full text |Cite
|
Sign up to set email alerts
|

Compliance with the aseptic precautions during intravenous access among the nursing staff at the National Hospital of Sri Lanka (NHSL)

Abstract: Intravenous access is one of the most commonly performed invasive procedures in the clinical practice, during which the improper practice of the aseptic precautions could lead to fatal healthcare associated infections. a descriptive cross sectional study was conducted to assess the compliance with aseptic precautions during intravenous access and to identify the determinants of the substandard practice and practical difficulties encountered at the National Hospital of Sri Lanka using a self administered questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 6 publications
2
7
0
Order By: Relevance
“…Similar to our study, the education level had no association with the adherence to the standard precautions among radiographers in a tertiary care hospital of Sri Lanka [17]. However, a Sri Lankan study conducted among the nursing staff at the same setting concluded that the junior nurses were more compliant on the standard precautions than the senior nursing staff, probably since the former have updated their knowledge recently [18].…”
Section: Discussionsupporting
confidence: 73%
“…Similar to our study, the education level had no association with the adherence to the standard precautions among radiographers in a tertiary care hospital of Sri Lanka [17]. However, a Sri Lankan study conducted among the nursing staff at the same setting concluded that the junior nurses were more compliant on the standard precautions than the senior nursing staff, probably since the former have updated their knowledge recently [18].…”
Section: Discussionsupporting
confidence: 73%
“…1,13,14 However hand hygiene is a single most effective preventive measure against hospital acquired infections, and can contribute to shorter hospital stay, reduction in patient morbidity and health care costs. 1 It is important to carry out training programmes on hand hygiene regularly for health care workers as it has been associated with increased compliance to hand hygiene practices and reduction of infection.…”
Section: Discussionmentioning
confidence: 99%
“…5,9 In Asia there is a paucity of studies 10,11,12 exploring this subject, although the prevalence of health care associated infections is high in this region. In Sri Lanka, a study 13 conducted at the National Hospital of Sri Lanka (NHSL), showed that more than 60% of the nursing staff had substandard practices when it came to aseptic techniques including hand washing. It was also shown that nursing students, less experienced nurses and those who had recently got their knowledge updated were more likely to have better compliance with aseptic techniques.…”
Section: Introductionmentioning
confidence: 99%
“…12 Furthermore, several studies done to assess the knowledge, attitudes and compliance and reasons for non-adherence to hand hygiene guidelines revealed that compliance with hygiene protocols by health care workers is poor 13 , 14 , 15 due to several constraints, including heavy work load, high number of clinical procedures and skin conditions of health care worker. 16 , 17 It is alarming that compliance with general aseptic guidelines was found to be worse before high risk procedures were done. 14 , 18 Thus, the reported low or outright non-compliance of health care workers with the global best practices on the prevention of spread of hospital acquired infections and its associated morbidity and mortality makes this study a necessity.…”
Section: Introductionmentioning
confidence: 99%